Pola Komunikasi Komunitas Virtual ICB dalam Meminimalisasi Hoaks - Giyan Rahmat Rahmat (Academic Journal of Da'wa and Communication, 2022)
The purpose of this study is to describe ICB's communication pattern as a virtual community in an effort to minimize hoaxes. This is caused by ICB's position as a massive virtual community that uses Facebook as its communication medium. However, Facebook as a social media is a place for networking information with a wide range, so that it also allows the emergence of hoaxes in circulating information. This research used a descriptive qualitative method with data collection through observation, in-depth interviews, and documentation. This research finds that there are two models of communication patterns used by ICB, namely: the wheel communication pattern and the all-channel communication pattern. The wheel communication pattern includes filtering of uploaded information within the group, in which each member waits for approval from the admin to join or share uploads to the group, especially with a centralized flow at one point, so that the flow of incoming information is orderly and minimizes hoaxes within the group. Meanwhile, the communication patterns of all channels allow for more flexible community meetings and activities, in which each member can interact with anyone without any restrictions.